Analisis Festival Tanjung Lesung dalam Upaya Meningkatkan Wisatawan Pasca Tsunami - Novianthy Haniah; Sri Dewi Setiawati (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
This study aims to determine the marketing communication strategy of the Banten Province Tourism Office and to analyze the Tanjung Lesung Festival in an effort to increase post-tsunami tourists. This research method focuses on Philip Lesly's communication strategy planning model regarding analysis and research. The results of this study illustrate that the Banten Province Tourism Office held the Tanjung Lesung Festival in an effort to attract tourists to return to the Tanjung Lesung Special Economic Zone (SEZ). The conclusion of this research is that one of the marketing strategies is communication related to the Tanjung Lesung Festival. So that there are no obstacles in these activities by establishing good relations with the people in their fields Keywords: Event Management, Marketing Strategy, Strategy Communication, Communication, Tanjung Lesung